IMPLEMENTATION CHALLENGES AND OPPORTUNITIES CORETAX ADMINISTRATION SYSTEM ON THE EFFICIENCY OF TAX ADMINISTRATION - Arianty, Fitria (UI Scholars Hub, 2024)
An efficient and transparent tax administration system is essential to ensure the optimization of state revenue and taxpayer compliance. The Indonesian government has initiated the implementation of the Coretax Administration System (CtAS) as part of tax reform efforts to improve efficiency in tax administration. This study aims to analyze the challenges and opportunities faced in the process of implementing CtAS in Indonesia. This study uses a qualitative method with data collection techniques in the form of literature studies, which are continued by conducting a SWOT analysis of this CtAS policy. The results of the discussion show that the main challenges identified include the readiness of technological infrastructure, human resource adaptation, and resistance from taxpayers and tax authorities. On the other hand, opportunities that arise from the implementation of this system include increasing data accuracy, reducing administrative costs, and the potential for increasing tax revenue through better data integration and a more transparent reporting system. The results of the study are expected to provide strategic insights for the government and tax authorities in overcoming existing obstacles and maximizing the benefits of CtAS in improving the efficiency of tax administration in Indonesia. It is recommended for the Directorate General of Taxes to be able to identify ways to strengthen the CtAS policy that will be implemented, overcome existing weaknesses, and take advantage of available opportunities, as well as prepare mitigation steps and manage threats that may arise.